2022
DOI: 10.1002/marc.202200149
|View full text |Cite
|
Sign up to set email alerts
|

Role of Molecular Weight in the Mechanical Properties and Charge Transport of Conjugated Polymers Containing Siloxane Side Chains

Abstract: The molecular weight is a key factor affecting the properties of conjugated polymers. To determine the critical molecular weights of conjugated polymers modified with siloxane side chains, poly‐diketo‐pyrrolopyrrole‐selenophene (PTDPPSe‐5Si) samples with molecular weights ranging from 20 to 350 kDa are synthesized. The critical molecular weight of the polymer is determined in the range of 60–100 kDa by testing the viscosity of the solution. When the molecular weight of the 27–60 kDa polymers is below the criti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…In addition, the phenomenon of holes was observed, as the silicon in the siloxane side chains imparts strong hydrophobicity and low surface energy. During annealing, CP chains containing siloxane side chains are more prone to movement, leading to the formation of hole structures. , Although the pore structure created during annealing might lead to inferior electrical performance, more ordered stacking of the CP chains facilitates the transport of charge carriers. These two factors are in competition with each other.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the phenomenon of holes was observed, as the silicon in the siloxane side chains imparts strong hydrophobicity and low surface energy. During annealing, CP chains containing siloxane side chains are more prone to movement, leading to the formation of hole structures. , Although the pore structure created during annealing might lead to inferior electrical performance, more ordered stacking of the CP chains facilitates the transport of charge carriers. These two factors are in competition with each other.…”
Section: Resultsmentioning
confidence: 99%
“…Among various types of side chains, the linear siloxane side chains have a large cross-sectional area (41 Å 2 ) comparable to that of branched alkyl side chains due to the large bond angle (143°) and longer bond length (1.64 Å) of the −Si–O– bond. This enables them to regulate the aggregation structure of CPs and exhibit enormous potential for applications. , Recent studies have shown that the length of siloxane side chains, their density, and the molecular weight of CPs have a significant effect on the elastic properties of semiconductor polymer films. Siloxane side chains are heterogeneous side chains that require methylene-spaced side chains for concatenation since the siloxane groups are characterized by their chemical inertness and steric effects, making it challenging for them to directly attach to the backbone.…”
Section: Introductionmentioning
confidence: 99%
“…The superiorly stretchable conjugated polymer can be obtained by combining with backbone engineering, [16][17][18][19] side chain engineering, [20][21][22] and molecular weight controlling. [23,24] In the design and synthesis of intrinsically stretchable D-A polymer structures, the acceptor unit is usually investigated by introducing solubilizing side chains, as well as dynamic bonding units containing hydrogen bonds, and other functional side chains, such as biaxially extended conjugated side chain and oligosiloxane side chain. [25][26][27][28] On the other hand, the donor unit also controlled the conformation of the polymer and adjusted the stretchability of the film by tuning the number of rigid fused rings, or inserting free flexible nonconjugated spacers in the donor, and introducing side chains in the rigid fused rings of the donor.…”
Section: Introductionmentioning
confidence: 99%
“…The superiorly stretchable conjugated polymer can be obtained by combining with backbone engineering, [ 16–19 ] side chain engineering, [ 20–22 ] and molecular weight controlling. [ 23,24 ]…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the P A additive with a MW higher than the critical MW (M c ) can readily form entangled structures and provide tie molecules, which effectively bridge adjacent crystalline domains. [41][42][43][44][45][46] Furthermore, P A tie molecules can serve as additional conducting pathways between the SMA domains, facilitating charge transport in the P D :SMA-based active layer. For example, the effectiveness of an electro-active polymer additive was demonstrated by Zhu et al 47 Incorporating the highly crystalline D18 polymer into the PM6:L8-BO system enhanced the crystallinity of the blend lm by promoting the formation of brillar structures of the P D and SMA domains.…”
Section: Introductionmentioning
confidence: 99%